Analyzing tourist destinations in Belgrade using geotagged photos from Flickr - Milosavljević, Vera; Paliska, Dejan (Proceedings of the10th Student Computing Research Symposium (SCORES’24), 2024)
This research aims to analyze tourist destinations in Belgrade by defining trajectories of movement of the users of platform Flickr using geotagged photos on Flickr. We defined tourist movements and used generalization techniques to identify the main tourists locations. We applied several techniques to identify frequently visited locations and predict next possible tourist spots. Our findings provide insights into popular travel patterns and suggest potential areas for tourism development.